Strategi Spritualitas Qur’ani untuk Mengatasi FOMO pada Generasi Z - Shinta Shavira; Pitri Pardomuan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The development of social media platforms such as Instagram, TikTok, Facebook, and YouTube has resulted in a major transformation in the way people communicate and interact, especially among Generation Z. This generation, born between 1997 and 2012, was formed in a digital environment rich in information and high social interaction. This study aims to uncover the psychological impacts of excessive social media use, such as the emergence of feelings of fear of missing out (FoMO), anxiety, low self-confidence, and identity crisis. Various studies have shown that high frequency of social media use is closely related to increased social pressure and mental health disorders. From an Islamic perspective, the Qur'an as a guide for Muslims offers spiritual solutions that can help balance the challenges of this digital era. This research underlines the importance of a faith-based approach to addressing the negative impacts of social media, and invites the younger generation to return to Qur'anic values ​​in order to achieve inner peace and strengthen their relationship with Allah SWT.